Sunscreen compositions and methods for their preparation, sunscreen formulations

CN122997976APending Publication Date: 2026-10-30SHENZHEN MINUS TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610964254.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-06-30
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

当前主流防晒产品主要依赖化学防晒剂和物理防晒剂实现紫外线全波段防护,但两类防晒剂均存在显著技术缺陷:化学防晒剂存在透皮吸收的安全风险,且部分成分具有海洋生态毒性,不符合绿色环保的行业发展趋势;物理防晒剂如纳米二氧化钛、氧化锌等,需高添加量才能实现高倍防晒效果,易导致产品出现假白、肤感厚重粗糙等问题,同时高添加量也会增加配方成本,降低产品市场竞争力

Benefits of technology

[0047]本申请的防晒组合物采用本身并无明显防晒效果的氮化硼和硅石与化学防晒剂复合使用,通过控制各组分的质量分数、氮化硼和硅石的粒径及吸油值,基于氮化硼具有高折射率、化学惰性及片层结构的特性,结合硅石的微米级多孔结构对光线散射,可优化防晒膜的均匀性,两者复合协同增效,可显著提升防晒组合物对紫外线全波段的防护效率,在满足相同防晒值的效果下,相较于传统防晒组合物,可显著减少防晒制剂的使用量。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The application provides a sunscreen composition and a preparation method thereof, and belongs to the technical field of sunscreens. The sunscreen composition comprises the following components in mass fraction: 1-2% boron nitride, 2-6% silica, 15-25% chemical sunscreen agent, 10-30% additive, and 37-72% water; wherein the boron nitride satisfies: an average particle size of 6-12 mu m and an oil absorption value of 50-100 g / 100 g; and the silica satisfies: an average particle size of 3-7 mu m and an oil absorption value of 60-130 g / 100 g. By adopting the boron nitride, silica, chemical sunscreen agent, additive and water in certain mass fractions, and by controlling the particle size and oil absorption value of the boron nitride and silica, the sunscreen efficacy can be significantly improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the field of sun protection technology, and in particular to sun protection compositions and their preparation methods, and sun protection formulations. Background Technology

[0002] In the field of sun protection technology, consumers' demands for the protective efficacy, safety, and environmental friendliness of sun protection products continue to rise, driving the industry to shift from traditional sunscreen formulations to new composite formulas. Currently, mainstream sun protection products mainly rely on chemical and physical sunscreens to achieve full-spectrum UV protection. However, both types of sunscreens have significant technical drawbacks: chemical sunscreens pose a safety risk of transdermal absorption, and some ingredients have marine ecotoxicity, which does not align with the industry's green and environmentally friendly development trend; physical sunscreens, such as nano-titanium dioxide and zinc oxide, require high concentrations to achieve high SPF effects, which can easily lead to problems such as a white cast, a heavy and rough feel on the skin, and increased formulation costs, reducing product market competitiveness.

[0003] Therefore, how to improve the system of sunscreen agents to enhance their sun protection efficacy and improve the user experience has become an urgent technical problem to be solved. Summary of the Invention

[0004] Therefore, the main objective of this application is to provide sunscreen compositions and their preparation methods, as well as sunscreen formulations, to improve their sunscreen efficacy.

[0005] In a first aspect, this application provides a sunscreen composition comprising the following components by mass fraction:

[0006] 1%-2% boron nitride, 2%-6% silica, 15%-25% chemical sunscreen, 10%-30% additives and 37%-72% water;

[0007] The boron nitride described therein has the following properties: average particle size of 6μm-12μm and oil absorption value of 50 g / 100g-100 g / 100g.

[0008] The silica has the following characteristics: average particle size of 3μm-7μm and oil absorption value of 60 g / 100g-130 g / 100g.

[0009] In some embodiments, the boron nitride is boron nitride surface-treated with a polydimethylsiloxane derivative.

[0010] In some embodiments, the boron nitride surface-treated with the polydimethylsiloxane derivative includes PEG-12 polydimethylsiloxane.

[0011] In some embodiments, the sunscreen composition contains boron nitride at a mass fraction of 1%-1.5% and silica at a mass fraction of 3%-4.5%.

[0012] In some embodiments, the boron nitride satisfies the following conditions: an average particle size of 6 μm-12 μm and an oil absorption value of 50 g / 100g-60 g / 100g.

[0013] In some embodiments, the silica has the following characteristics: an average particle size of 3μm-7μm and an oil absorption value of 90 g / 100g-100g / 100g.

[0014] In some embodiments, the chemical sunscreen agent includes at least one selected from ethylhexyl p-methoxycinnamate, butyl methoxydibenzoylmethane, benzyl camphor sulfonic acid and its salts, bis-ethylhexyloxyphenol methoxyphenyl triazine, camphor benzalkonium methyl sulfate, diethylaminohydroxybenzoylhexyl benzoate, diethylhexylbutamidotriazinone, disodium phenyl dibenzimidazole tetrasulfonate, cresoltrazol trisiloxane, dimethyl PABA ethylhexyl ester, ethylhexyl salicylate, ethylhexyl triazinone, humosasulfate, isoamyl p-methoxycinnamate, methylene bis-benzotriazolyl tetramethylbutylphenol, PEG-25 p-aminobenzoic acid, phenyl benzyl mitomazole sulfonic acid and its salts, polyacrylamide methyl benzyl camphor, and polysiloxane-15.

[0015] In some embodiments, the sunscreen composition further includes 2%-5% by mass of a physical sunscreen agent; the physical sunscreen agent includes at least one of nano-titanium dioxide, nano-cerium dioxide, and nano-iron oxide.

[0016] In some embodiments, the adjuvant includes at least one of humectants, film-forming agents, skin-moisturizers, emulsifiers, thickeners, and preservatives.

[0017] In some embodiments, the humectant includes at least one of butylene glycol, glycerin, and propylene glycol.

[0018] In some embodiments, the film-forming agent includes at least one of polydimethylsiloxane, acrylate copolymers, and polyurethane copolymers.

[0019] In some embodiments, the emollient includes at least one selected from diisopropyl sebacate, cetearyl alcohol, butyl octyl salicylate, C12-15 benzoate, and dibutyl adipate.

[0020] In some embodiments, the emulsifier includes at least one of cetyl phosphate potassium, cetearyl glucoside, and sodium stearoyl glutamate.

[0021] In some embodiments, the thickener includes at least one selected from sodium polyacrylate, xanthan gum, carbomer, hydroxyethyl cellulose, acrylate, guar gum, and gum arabic.

[0022] In some embodiments, the preservative includes at least one selected from phenoxyethanol, octyl glycol, ethylhexylglycerin, 1,2-pentanediol, and hexanediol.

[0023] Secondly, this application also provides a method for preparing a sunscreen composition, comprising the following steps:

[0024] Mix the chemical sunscreen, film-forming agent, and emollient evenly to prepare solution A;

[0025] Physical sunscreen and silica are added to solution A and mixed evenly to prepare composition A;

[0026] After mixing water, emulsifier, humectant, preservative A and thickener A, boron nitride is added and mixed evenly to prepare solution B;

[0027] The composition A is added to the solution B and homogenized and emulsified. Then, thickener B is added and homogenization is continued. After all components are emulsified and dispersed evenly, the mixture is stirred and cooled. During the stirring and cooling process, preservative B is added, and stirring and cooling are continued to prepare the sunscreen composition.

[0028] In the sunscreen composition, the mass fraction of boron nitride is 1%-2%, the mass fraction of silica is 2%-6%, and the mass fraction of chemical sunscreen agent is 15%-25%.

[0029] The boron nitride meets the following requirements: average particle size of 6μm-12μm, and oil absorption value of 50 g / 100g-100 g / 100g;

[0030] The silica has the following characteristics: average particle size of 3μm-7μm and oil absorption value of 60 g / 100g-130 g / 100g.

[0031] In some embodiments, the chemical sunscreen agent includes at least one of ethylhexyl salicylate, ethylhexyl methoxycinnamate, bis-ethylhexyloxyphenol methoxyphenyl triazine, ethylhexyl triazine ketone, methylene bis-benzotriazolyl tetramethylbutylphenol, and polysiloxane-15.

[0032] And / or, the film-forming agent includes polydimethylsiloxane;

[0033] And / or, the emollient includes diisopropyl sebacic acid and cetearyl alcohol;

[0034] And / or, the physical sunscreen agent includes nano-titanium dioxide;

[0035] And / or, in the sunscreen composition, the mass fraction of the physical sunscreen agent is 2%-5%;

[0036] And / or, the emulsifier includes potassium cetyl phosphate;

[0037] And / or, the humectant includes butylene glycol;

[0038] And / or, the preservative A includes octyl glycol;

[0039] And / or, the thickener A includes xanthan gum;

[0040] And / or, the boron nitride is boron nitride surface-treated with PEG-12 polydimethylsiloxane;

[0041] And / or, the thickener B comprises sodium polyacrylate;

[0042] And / or, the preservative B includes phenoxyethanol;

[0043] And / or, the boron nitride satisfies the following conditions: average particle size of 6μm-12μm, and oil absorption value of 50 g / 100g-60 g / 100g;

[0044] And / or, the silica satisfies the following conditions: an average particle size of 3μm-7μm and an oil absorption value of 90 g / 100g-100 g / 100g. Thirdly, this application also provides a sunscreen formulation, the raw materials of which include: the sunscreen composition described in the first aspect or a sunscreen composition prepared by the method described in the second aspect.

[0045] In some embodiments, the sunscreen formulation includes an emulsion or a cream.

[0046] Compared with traditional technologies, this application has at least the following beneficial effects:

[0047] The sunscreen composition of this application uses boron nitride and silica, which do not have obvious sun protection effects on their own, in combination with chemical sunscreen agents. By controlling the mass fraction of each component, the particle size of boron nitride and silica, and the oil absorption value, the uniformity of the sunscreen film can be optimized by combining the high refractive index, chemical inertness and lamellar structure of boron nitride with the micron-sized porous structure of silica to scatter light. The combination of the two has a synergistic effect, which can significantly improve the protection efficiency of the sunscreen composition against the entire ultraviolet spectrum. Compared with traditional sunscreen compositions, it can significantly reduce the amount of sunscreen agent used while achieving the same sun protection value. Detailed Implementation

[0048] The present application will be further described in detail below with reference to the embodiments and examples. These embodiments and examples are for illustrative purposes only and are not intended to limit the scope of the present application. The purpose of providing these embodiments and examples is to enable a more thorough and comprehensive understanding of the disclosure of the present application. It should also be understood that the present application can be implemented in many different forms and is not limited to the embodiments and examples described herein. Those skilled in the art can make various modifications or alterations without departing from the spirit of the present application, and the equivalent forms obtained also fall within the protection scope of the present application. Furthermore, numerous specific details are set forth in the following description to provide a fuller understanding of the present application. It should be understood that the present application can be implemented without one or more of these details.

[0049] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this application belongs. The terminology used herein is for the purpose of describing particular embodiments only and is not intended to be limiting of the application. The term "and / or" as used herein includes any and all combinations of one or more of the associated listed items.

[0050] To address the issues of poor sun protection efficacy and high amounts of sunscreen agents in traditional sunscreen products, the sunscreen composition of this application significantly improves its sun protection efficacy and enhances its protection efficiency across the entire UV spectrum by using a certain mass fraction of boron nitride, silica, chemical sunscreen agents, additives, and water, and by controlling the particle size and oil absorption value of boron nitride and silica, thereby reducing the amount of sunscreen agent used.

[0051] In a first aspect, this application provides a sunscreen composition comprising the following components by mass fraction:

[0052] 1%-2% boron nitride, 2%-6% silica, 15%-25% chemical sunscreen, 10%-30% additives and 37%-72% water;

[0053] The boron nitride described therein has the following properties: average particle size of 6μm-12μm and oil absorption value of 50 g / 100g-100 g / 100g.

[0054] The silica has the following characteristics: average particle size of 3μm-7μm and oil absorption value of 60 g / 100g-130 g / 100g.

[0055] In this application, the boron nitride is a layered or sheet-like two-dimensional sheet structure, and its sheets have a certain thickness and aspect ratio.

[0056] The boron nitride particles themselves are silky and soft, which can effectively reduce the friction of the sunscreen composition during the application process, allowing the product to spread more smoothly and evenly on the skin surface, further ensuring the integrity of the sunscreen film and indirectly improving the sun protection value.

[0057] In this application, the silica is spherical with tiny micropores distributed on its surface, giving it a certain oil-absorbing capacity. This application uses spherical silica with a particle size of 3-7 μm. Smaller silica particles have a larger specific surface area, significantly improving sun protection efficacy. However, this also greatly reduces ultraviolet scattering efficiency, resulting in a very poor improvement in SPF. When used in the sunscreen composition, the micron-sized spherical structure and specific oil-absorbing value of the silica enable it to efficiently scatter ultraviolet rays directed towards the skin surface. This causes the originally directly incident ultraviolet rays to undergo multiple reflections and refractions, significantly extending the light path of ultraviolet rays within the sunscreen film. This increases the contact opportunity between ultraviolet rays and chemical sunscreen agents, allowing the chemical sunscreen agents to more fully absorb ultraviolet rays, significantly reducing the intensity of ultraviolet rays reaching the skin surface, and achieving a significant improvement in SPF.

[0058] Meanwhile, this application uses silica with an oil absorption value of 60 g / 100g-130 g / 100g, which can effectively absorb excess oil from the skin surface and the sunscreen composition, reducing the greasy feeling after applying the sunscreen composition and improving user experience. It also avoids problems caused by excessively high oil absorption values, such as excessive absorption of organic sunscreen agents and oils, reduced UV absorption efficiency of chemical sunscreen agents, and precipitation of crystalline sunscreen agents, thus preventing a decrease in SPF. Furthermore, silica is inexpensive and readily available, achieving high-efficiency sun protection without increasing the raw material cost of the formulation. Compared to existing high-priced active ingredient enhancement technologies, it is more suitable for large-scale industrial production.

[0059] Therefore, the sunscreen composition of this application uses boron nitride and silica, which do not have obvious sunscreen effect on their own, in combination with chemical sunscreen agents. By controlling the mass fraction of each component, the particle size of boron nitride and silica, and the oil absorption value, the uniformity of the sunscreen film can be optimized by combining the high refractive index, chemical inertness and lamellar structure of boron nitride with the micron-sized porous structure of silica to scatter light. The combination of the two has a synergistic effect, which can significantly improve the protection efficiency of the sunscreen composition against the entire ultraviolet spectrum. Compared with traditional sunscreen compositions, it can significantly reduce the amount of sunscreen agent used while achieving the same sun protection value.

[0060] Specifically, in the embodiments of this application, the boron nitride has a sheet-like or layered structure.

[0061] In some embodiments, the boron nitride is boron nitride surface-treated with a polydimethylsiloxane derivative. Surface treatment with a polydimethylsiloxane derivative effectively enhances the interfacial affinity between boron nitride and the silica surface, allowing them to interpenetrate and distribute evenly within the sunscreen system. When the sunscreen composition is used, a composite protective layer is formed on the skin surface, consisting of interwoven boron nitride sheets and silica spherical particles. When exposed to external light, the boron nitride surface-treated with the polydimethylsiloxane derivative enhances the physical sunscreen efficacy of the sunscreen composition through light scattering.

[0062] In some embodiments, the boron nitride surface-treated with a polydimethylsiloxane derivative includes PEG-12 polydimethylsiloxane. This application achieves hydrophilic modification of boron nitride by surface treatment with PEG-12 polydimethylsiloxane, resulting in a boron nitride surface that is both hydrophilic and oleophilic, enabling it to form good compatibility with both the oil and aqueous phases of an oil-in-water / water-in-oil emulsion system.

[0063] In some embodiments, the mass fraction of boron nitride in the sunscreen composition is 1%-2%, which can be 1%, 1.1%, 1.2%, 1.5%, 1.8% or 2.0%.

[0064] In some embodiments, the mass fraction of silica in the sunscreen composition is 2%-6%, which can be 2%, 3%, 4%, 5% or 6%.

[0065] This application significantly improves sun protection efficacy by controlling the amount of silica in the sunscreen composition and using silica in combination with boron nitride for synergistic effect. However, if the amount of silica in the sunscreen composition is too high, it can easily cause friction with the skin or absorb skin oils, resulting in skin discomfort and affecting the user experience.

[0066] In some embodiments, the mass fraction of boron nitride in the sunscreen composition is 1%-1.5%, which can be 1%, 1.1%, 1.2%, 1.3%, 1.4% or 1.5%; and the mass fraction of silica is 3%-4.5%, which can be 3%, 3.2%, 3.5%, 4%, 4.2% or 4.5%.

[0067] In some embodiments, the boron nitride satisfies the following conditions: an average particle size of 6μm-12μm and an oil absorption value of 50 g / 100g-60 g / 100g, which can be 50 g / 100g, 52 g / 100g, 55 g / 100g, 58 g / 100g or 60 g / 100g.

[0068] In some embodiments, the silica has the following characteristics: an average particle size of 3μm-7μm and an oil absorption value of 90 g / 100g-100g / 100g, which can be 90 g / 100g, 92 g / 100g, 95 g / 100g, 98 g / 100g or 100 g / 100g.

[0069] In some embodiments, the chemical sunscreen agent includes at least one selected from ethylhexyl p-methoxycinnamate, butyl methoxydibenzoylmethane, benzyl camphor sulfonic acid and its salts, bis-ethylhexyloxyphenol methoxyphenyl triazine, camphor benzalkonium methyl sulfate, diethylamino hydroxybenzoyl hexyl benzoate, diethylhexylbutamidotriazinone, disodium phenyl dibenzimidazole tetrasulfonate, cresoltrazol trisiloxane, dimethyl PABA ethylhexyl ester, ethylhexyl salicylate, ethylhexyl triazinone, humosasulfate, isoamyl p-methoxycinnamate, methylene bis-benzotriazolyl tetramethylbutylphenol, PEG-25 p-aminobenzoic acid, phenyl benzyl mitomazole sulfonic acid and its salts, polyacrylamide methyl benzyl camphor, and polysiloxane-15.

[0070] In some embodiments, the adjuvant includes at least one of humectants, film-forming agents, skin-moisturizers, emulsifiers, thickeners, and preservatives.

[0071] In some embodiments, the humectant includes at least one of butylene glycol, glycerin, and propylene glycol.

[0072] In some embodiments, the film-forming agent includes at least one of polydimethylsiloxane, acrylate copolymers, and polyurethanes.

[0073] In some embodiments, the emollient includes at least one selected from diisopropyl sebacate, cetearyl alcohol, butyl octyl salicylate, C12-15 benzoate, and dibutyl adipate.

[0074] In some embodiments, the emulsifier includes at least one of cetyl phosphate potassium, cetearyl glucoside, and sodium stearoyl glutamate.

[0075] In some embodiments, the thickener includes at least one selected from sodium polyacrylate, xanthan gum, carbomer, hydroxyethyl cellulose, acrylate, guar gum, and gum arabic.

[0076] In some embodiments, the preservative includes at least one selected from phenoxyethanol, octyl glycol, ethylhexylglycerin, 1,2-pentanediol, and hexanediol.

[0077] In some embodiments, the sunscreen composition further includes 2%-5% by mass of a physical sunscreen agent; the physical sunscreen agent includes at least one of nano-titanium dioxide, nano-cerium dioxide, and nano-iron oxide.

[0078] Physical sunscreens, due to their high surface energy, readily adsorb and aggregate to form large-diameter agglomerates. When boron nitride is dispersed in a sunscreen composition, its lamellar structure is randomly interspersed between the physical sunscreen particles, forming a physical barrier layer. Specifically, in the sunscreen composition, boron nitride lamellars are adsorbed on the surface of the physical sunscreen particles or fill the gaps between the particles, separating the originally close physical sunscreen particles, reducing the van der Waals attraction between the particles, and preventing the formation of agglomerates.

[0079] Meanwhile, boron nitride sheets themselves have good dispersibility. Under the action of stirring, homogenization and other processes, they can be uniformly dispersed in the oil / water phase to form a continuous dispersion medium network. Boron nitride can be anchored to the surface of sunscreen particles through interfacial adsorption to form a "compatibility shell". This "wraps" the physical sunscreen particles and fixes them in the gaps between the networks. This is beneficial to improving the wettability of sunscreen particles in the formulation system and maintaining the monodisperse / microdisperse state of physical sunscreen particles, preventing them from settling and agglomerating during storage and production.

[0080] This application ensures the steric hindrance effect of the film by controlling the particle size of boron nitride within the range of 6-12 μm, forming a particle size distribution with the nano-sized physical sunscreen particles, further improving the stability of the dispersion system. If the particle size of boron nitride is too large or too small, it is prone to agglomeration, making it difficult to achieve uniform dispersion. Applying this to sunscreen formulations carries the risk of reducing the uniformity of the sunscreen film, affecting the continuity and stability of sun protection, and reducing user comfort.

[0081] Furthermore, the silica in this application is spherical silica. When used in the sunscreen composition, the micron-sized spherical structure and specific oil absorption value of silica enable it to have a highly efficient scattering effect on ultraviolet rays that are directed toward the skin surface. This causes the originally directly incident ultraviolet rays to be reflected and refracted multiple times, greatly extending the light path of ultraviolet rays in the sunscreen film and making the physical sunscreen agent more effective at blocking ultraviolet rays.

[0082] In some embodiments, the sunscreen composition comprises the following components by mass fraction:

[0083] 1%-2% boron nitride, 2%-6% silica, 15%-25% chemical sunscreen, 2%-5% physical sunscreen, 10%-30% additives and the balance being water.

[0084] In some embodiments, the sunscreen composition comprises: a chemical sunscreen agent consisting of ethylhexyl salicylate, ethylhexyl methoxycinnamate, bis-ethylhexyloxyphenol methoxyphenyl triazine, ethylhexyl triazine ketone, methylene bis-benzotriazolyl tetramethylbutylphenol, and polysiloxane-15; a film-forming agent consisting of polydimethylsiloxane; a skin-moisturizing agent consisting of diisopropyl sebacate and cetearyl alcohol; an emulsifier consisting of potassium cetyl phosphate; a thickener consisting of sodium polyacrylate and xanthan gum; a preservative consisting of phenoxyethanol and octyl glycol; a physical sunscreen agent consisting of nano-titanium dioxide; and a moisturizing agent consisting of butylene glycol.

[0085] A second aspect of this application provides a method for preparing a sunscreen composition, comprising the following steps:

[0086] Mix the chemical sunscreen, film-forming agent, and emollient evenly to prepare solution A;

[0087] Physical sunscreen and silica are added to the solution and mixed evenly to prepare composition A;

[0088] After mixing water, emulsifier, humectant, preservative A and thickener A, boron nitride is added and mixed evenly to prepare solution B;

[0089] The composition A is added to the solution B and homogenized and emulsified. Then, thickener B is added and homogenization is continued. After all components are emulsified and dispersed evenly, the mixture is stirred and cooled. During the stirring and cooling process, preservative B is added, and stirring and cooling are continued to prepare the sunscreen composition.

[0090] In the sunscreen composition, the mass fraction of boron nitride is 1%-2%, the mass fraction of silica is 2%-6%, and the mass fraction of chemical sunscreen agent is 15%-25%.

[0091] The boron nitride meets the following requirements: average particle size of 6μm-12μm, and oil absorption value of 50 g / 100g-100 g / 100g;

[0092] The silica has the following characteristics: average particle size of 3μm-7μm and oil absorption value of 60 g / 100g-130 g / 100g.

[0093] In some embodiments, the chemical sunscreen agent includes at least one of ethylhexyl salicylate, ethylhexyl methoxycinnamate, bis-ethylhexyloxyphenol methoxyphenyl triazine, ethylhexyl triazine ketone, methylene bis-benzotriazolyl tetramethylbutylphenol, and polysiloxane-15.

[0094] And / or, the film-forming agent includes polydimethylsiloxane;

[0095] And / or, the emollient includes diisopropyl sebacic acid and cetearyl alcohol;

[0096] And / or, the physical sunscreen agent includes nano-titanium dioxide;

[0097] And / or, in the sunscreen composition, the mass fraction of the physical sunscreen agent is 2%-5%;

[0098] And / or, the emulsifier includes potassium cetyl phosphate;

[0099] And / or, the humectant includes butylene glycol;

[0100] And / or, the preservative A includes octyl glycol;

[0101] And / or, the thickener A includes xanthan gum;

[0102] And / or, the boron nitride is boron nitride surface-treated with PEG-12 polydimethylsiloxane;

[0103] And / or, the thickener B comprises sodium polyacrylate;

[0104] And / or, the preservative B includes phenoxyethanol;

[0105] And / or, the boron nitride satisfies the following conditions: average particle size of 6μm-12μm, and oil absorption value of 50 g / 100g-60 g / 100g;

[0106] And / or, the silica satisfies the following conditions: average particle size of 3μm-7μm, and oil absorption value of 90 g / 100g-100 g / 100g.

[0107] In some embodiments, the mixing temperature during the preparation of solution A is 83-87°C.

[0108] In some embodiments, the mixing temperature during the preparation of solution B is 68-72°C.

[0109] In some embodiments, the mass fraction of silica in the sunscreen composition is 2%-6%, which can be 2%, 3%, 4%, 5% or 6%.

[0110] In some embodiments, the mass fraction of the chemical sunscreen agent in the sunscreen composition is 15%-25%, which can be 15%, 18%, 20%, 22% or 25%.

[0111] In some embodiments, the chemical sunscreen agent includes ethylhexyl salicylate, ethylhexyl methoxycinnamate, bis-ethylhexyloxyphenol methoxyphenyl triazine, ethylhexyl triazine ketone, methylene bis-benzotriazolyl tetramethylbutylphenol, and polysiloxane-15.

[0112] In some embodiments, the chemical sunscreen agent in the sunscreen composition comprises the following components by mass fraction:

[0113] 3% ethylhexyl salicylate, 8% ethylhexyl methoxycinnamate, 2% bis-ethylhexyloxyphenol methoxyphenyl triazine, 1.5% ethylhexyl triazine ketone, 2% methylene bis-benzotriazolyl tetramethyl butylphenol and 3.5% polysiloxane-15.

[0114] In some embodiments, the sunscreen composition comprises the following components by mass fraction:

[0115] 5.5% moisturizer, 3% film-forming agent, 3% emollient, 2% emollient, 2% emulsifier, 0.2% thickener A, 0.2% thickener B, 0.3% preservative A and 0.8% preservative B.

[0116] In some embodiments, the chemical sunscreen agent is a composition of ethylhexyl salicylate, ethylhexyl methoxycinnamate, bis-ethylhexyloxyphenol methoxyphenyl triazine, ethylhexyl triazine ketone, methylene bis-benzotriazolyl tetramethylbutylphenol, and polysiloxane-15; the film-forming agent is polydimethylsiloxane; the emollient is diisopropyl sebacate and cetearyl alcohol; the physical sunscreen agent is nano-titanium dioxide; the emulsifier is potassium cetyl phosphate; the moisturizer is butylene glycol; the preservative consists of preservative A and preservative B, where preservative A is octyl glycol and preservative B is phenoxyethanol; the thickener consists of thickener A and thickener B, where thickener A is xanthan gum and thickener B is sodium polyacrylate; and the boron nitride is boron nitride surface-treated with PEG-12 polydimethylsiloxane.

[0117] The preparation method of the chemical sunscreen composition is as follows:

[0118] S1. Add ethylhexyl salicylate, ethylhexyl methoxycinnamate, bis-ethylhexyloxyphenol methoxyphenyl triazine, ethylhexyl triazine ketone, methylene bis-benzotriazolyl tetramethyl butylphenol, polysiloxane-15, polydimethylsiloxane, diisopropyl sebacate, and cetearyl alcohol to an oil phase stirred tank, heat to 85±2℃, and stir at 300 r / min until completely dissolved to prepare solution A;

[0119] S2. Add nano-titanium dioxide and silica to the first solution, adjust the rotation speed to 1500 r / min, and disperse at high speed for 30 min until the system is free of particles to prepare composition A;

[0120] S3. Add water, potassium cetyl phosphate, butanediol, octyl glycol and xanthan gum to an aqueous phase stirred tank, heat to 70±2℃, stir at 400 r / min until completely dissolved, then add boron nitride surface treated with PEG-12 polydimethylsiloxane, adjust the speed to 1200 r / min, disperse at high speed for 25 min until uniform, and prepare solution B;

[0121] S4. Slowly add the composition A to the solution B through a delivery pump, homogenize and emulsify at a speed of 3000 r / min for 15 min, then add sodium polyacrylate and continue homogenizing for 5 min. After all components are emulsified and dispersed evenly, turn on the cooling system and stir and cool at a rate of 5℃ / h.

[0122] S5. Add phenoxyethanol when the temperature drops to 40°C, continue stirring at 200 r / min and cool to 30 ± 2°C to prepare the sunscreen composition. In some embodiments, the prepared sunscreen composition is the sunscreen composition described in the first aspect.

[0123] Thirdly, this application also provides a sunscreen formulation, the raw materials of which include the sunscreen composition described in the first aspect or the sunscreen composition prepared by the method described in the second aspect.

[0124] In some embodiments, the sunscreen formulation includes an emulsion or a cream.

[0125] The present invention will be further described in detail below with reference to specific embodiments. These embodiments are only used to explain the present invention and do not limit the scope of protection of the present invention. The raw materials used in the present invention are all commercially available conventional raw materials. For example, boron nitride can be a powder product from different manufacturers. In the test methods used, the in vitro sun protection value is tested using a Labsphere UV-2000S ultraviolet analyzer according to the COLIPA 2011 standard method.

[0126] In this application, the raw materials used in the embodiments and comparative examples are as follows:

[0127] Boron nitride 1: Powder with an average particle size of 1μm, an oil absorption value of 60g / 100g, a sun protection factor (SPF) of 1.02, and a UVA protection ratio of 0.82. It is boron nitride surface-treated with PEG-12 polydimethylsiloxane. The boron nitride 1 is purchased from the "Kingbornit aq 500" series products of Liankai Powder Company.

[0128] Boron nitride 2: Powder with an average particle size of 6μm, an oil absorption value of 50g / 100g, a sun protection factor (SPF) of 0.92, and an ultraviolet A (UVA) protection ratio of 0.99. It is boron nitride surface-treated with PEG-12 polydimethylsiloxane. The boron nitride 2 is purchased from the "Kingbornit aq 500" series products of Liankai Powder Company.

[0129] Boron nitride 3: powder with an average particle size of 12μm, an oil absorption value of 57g / 100g, a sun protection factor (SPF) of 1.10, and a UVA protection ratio of 0.98. It is boron nitride surface-treated with PEG-12 polydimethylsiloxane. The boron nitride 2 is a "Kingbornit aq 500" series product purchased from Liankai Powder Company.

[0130] Silica 1: Spherical particles, average particle size 3μm, oil absorption value 90 g / 100g, sun protection factor (SPF) 1.02, UVA protection ratio 1.01;

[0131] Silica 2: Spherical particles with an average particle size of 7μm, an oil absorption value of 100 g / 100g, a sun protection factor (SPF) of 0.98, and a UVA protection ratio of 0.87.

[0132] Silica 3: Spherical particles with an average particle size of 12μm, an oil absorption value of 100 g / 100g, a sun protection factor (SPF) of 0.72, and a UVA protection ratio of 0.81.

[0133] Silica 4: Spherical particles with an average particle size of 7μm, an oil absorption value of 300 g / 100g, a sun protection factor (SPF) of 0.89, and a UVA protection ratio of 0.72.

[0134] In this application, a Labsphere UV-2000S ultraviolet analyzer was used to test the sun protection factor (SPF) according to the COLIPA 2011 standard method. The SPF values ​​of boron nitride 1-boron nitride 3 and silica 1-silica 4 ranged from 0.72 to 1.02, indicating that boron nitride 1, boron nitride 2, boron nitride 3, silica 1, silica 2, silica 3, and silica 4 themselves do not possess significant independent sun protection effects. In this application, the oil absorption value was determined using the centrifugal oil absorption value determination method. The core principle of the test is: by mixing the test sample with excess oil, the test sample is allowed to fully absorb the oil. Then, the unabsorbed free oil is separated by centrifugation. The amount of oil adsorbed can be obtained by calculating the difference between the initial oil amount and the free oil amount, which yields the number of grams of oil adsorbed per gram of test sample.

[0135] Specifically, the oil absorption value is tested as follows:

[0136] The raw material to be tested was placed in a desiccator for 24 hours to equilibrate its moisture content. Castor oil (density 0.95 g / cm³) was used as the oil. 3 Accurately weigh 1.0 g of dried analyte into a centrifuge tube, then add an excess of oil, typically 10 times the amount of analyte (e.g., 1 g analyte to 10 mL oil). Ensure the analyte is completely submerged in oil. Gently stir with a glass rod or small spatula to ensure thorough mixing and a homogeneous suspension. Avoid vigorous stirring that could break up powder particles. Seal the centrifuge tube to prevent solvent evaporation and contamination. Incubate the centrifuge tube at room temperature (25°C) for 60 minutes to allow the analyte to fully adsorb the oil. Gently shake or stir every 10 minutes during this period. After incubation, centrifuge the suspension at the set centrifugal force (5000 g, 25°C, 30 minutes) to completely separate the unadsorbed free oil from the oil-adsorbed analyte. Collect the precipitate and accurately weigh the precipitate (i.e., the analyte after oil adsorption) (W1).

[0137] The oil absorption value is calculated based on the amount of oil adsorbed by the analyte and the mass of the analyte.

[0138] Oil absorption value (g / 100g) = 100 * (W1 - 1).

[0139] Three parallel experiments were conducted, and the average value was taken as the oil absorption value of the test substance.

[0140] Example 1

[0141] The sunscreen composition consists of the following components by mass fraction:

[0142] 1% boron nitride, 2% silica, 20% chemical sunscreen, 2% physical sunscreen (nano titanium dioxide), 17% additives and 58% water.

[0143] In the sunscreen composition, 20% by weight of the chemical sunscreen agent consists of the following components by weight:

[0144] 3% ethylhexyl salicylate, 8% ethylhexyl methoxycinnamate, 2% bis-ethylhexyloxyphenol methoxyphenyl triazine, 1.5% ethylhexyl triazine ketone, 2% methylene bis-benzotriazolyl tetramethyl butylphenol and 3.5% polysiloxane-15.

[0145] In the sunscreen composition, 17% by weight of the auxiliary agent consists of the following components by weight:

[0146] It consists of 5.5% humectant (butylene glycol), 3% film-forming agent (polydimethylsiloxane), 3% emollient (diisopropyl sebacic acid), 2% emollient (cetearearyl alcohol), 2% emulsifier (potassium cetyl phosphate), 0.2% thickener A (xanthan gum), 0.2% thickener B (sodium polyacrylate), 0.3% preservative A (caprylyl glycol), and 0.8% preservative B (phenoxyethanol).

[0147] The chemical sunscreen composition is prepared by the following method:

[0148] S1. Add ethylhexyl salicylate, ethylhexyl methoxycinnamate, bis-ethylhexyloxyphenol methoxyphenyl triazine, ethylhexyl triazine ketone, methylene bis-benzotriazolyl tetramethyl butylphenol, polysiloxane-15, polydimethylsiloxane, diisopropyl sebacate, and cetearyl alcohol to an oil phase stirred tank, heat to 85±2℃, and stir at 300 r / min until completely dissolved to prepare solution A;

[0149] S2. Add nano-titanium dioxide and silica to the first solution, adjust the rotation speed to 1500 r / min, and disperse at high speed for 30 min until the system is free of particles to prepare composition A;

[0150] S3. Add water, potassium cetyl phosphate, butanediol, octyl glycol and xanthan gum to an aqueous phase stirred tank, heat to 70±2℃, stir at 400 r / min until completely dissolved, then add boron nitride surface treated with PEG-12 polydimethylsiloxane, adjust the speed to 1200 r / min, disperse at high speed for 25 min until uniform, and prepare solution B;

[0151] S4. Slowly add the composition A to the solution B through a delivery pump, homogenize and emulsify at a speed of 3000 r / min for 15 min, then add sodium polyacrylate and continue homogenizing for 5 min. After all components are emulsified and dispersed evenly, turn on the cooling system and stir and cool at a rate of 5℃ / h.

[0152] S5. When the temperature drops to 40°C, add phenoxyethanol, continue stirring at 200 r / min and cool to 30±2°C to prepare the sunscreen composition.

[0153] Example 2

[0154] The sunscreen composition in Example 2 is essentially the same as that in Example 1, except that the amounts of silica 1 and water are different. Specifically, the sunscreen composition consists of the following components in the indicated mass fractions:

[0155] 1% boron nitride, 2% silica, 1% chemical sunscreen, 2% physical sunscreen (nano titanium dioxide), 17% additives and 57% water.

[0156] The sunscreen composition was prepared according to the method of Example 1.

[0157] Example 3

[0158] The sunscreen composition in Example 3 is essentially the same as that in Example 1, except that the amounts of silica 1 and water are different. Specifically, the sunscreen composition consists of the following components in the indicated mass fractions:

[0159] 1% boron nitride, 4% silica, 20% chemical sunscreen, 2% physical sunscreen (nano titanium dioxide), 17% additives and 56% water.

[0160] The sunscreen composition was prepared according to the method of Example 1.

[0161] Example 4

[0162] The sunscreen composition in Example 4 is essentially the same as that in Example 1, except that the amounts of silica 1 and water are different. Specifically, the sunscreen composition consists of the following components in the indicated mass fractions:

[0163] 1% boron nitride 2%, 5% silica 1%, 20% chemical sunscreen, 2% physical sunscreen (nano titanium dioxide), 17% additives and 55% water.

[0164] The sunscreen composition was prepared according to the method of Example 1.

[0165] Example 5

[0166] The sunscreen composition in Example 5 is essentially the same as that in Example 1, except that the amounts of silica 1 and water are different. Specifically, the sunscreen composition consists of the following components in the indicated mass fractions:

[0167] 1% boron nitride 2%, 6% silica 1%, 20% chemical sunscreen, 2% physical sunscreen (nano titanium dioxide), 17% additives and 54% water.

[0168] The sunscreen composition was prepared according to the method of Example 1.

[0169] Example 6

[0170] The sunscreen composition in Example 6 is essentially the same as that in Example 1, except for the amount of boron nitride 2 and water. Specifically, the sunscreen composition consists of the following components in the indicated mass fractions:

[0171] 2% boron nitride, 2% silica, 20% chemical sunscreen, 2% physical sunscreen (nano titanium dioxide), 17% additives and 57% water.

[0172] The sunscreen composition was prepared according to the method of Example 1.

[0173] Example 7

[0174] The sunscreen composition in Example 7 is basically the same as that in Example 1, except that the types and amounts of boron nitride and silica, and the amount of water are different.

[0175] Specifically, the sunscreen composition consists of the following components by mass fraction:

[0176] 1% boron nitride 3%, 5% silica 2%, 20% chemical sunscreen, 2% physical sunscreen (nano titanium dioxide), 17% additives and 55% water.

[0177] The sunscreen composition was prepared according to the method of Example 1.

[0178] Comparative Example 1

[0179] The sunscreen composition of Comparative Example 1 is basically the same as that of Example 1, except that boron nitride 2 and silica 1 are replaced with an equal amount of water.

[0180] The sunscreen composition was prepared according to the method of Example 1.

[0181] Comparative Example 2

[0182] The sunscreen composition of Comparative Example 2 is essentially the same as that of Example 1, except that "1% boron nitride 2%, 2% silica 1%, 58% water" is replaced with "5% boron nitride 1%, 56% water". Specifically, the sunscreen composition consists of the following components by mass fraction:

[0183] 5% boron nitride, 20% chemical sunscreen, 2% physical sunscreen (nano titanium dioxide), 17% additives and 56% water.

[0184] The sunscreen composition was prepared according to the method of Example 1.

[0185] Comparative Example 3

[0186] The sunscreen composition of Comparative Example 3 is essentially the same as that of Example 1, except that silica 1 is replaced with an equal mass of water. Specifically, the sunscreen composition consists of the following components by mass fraction:

[0187] 1% boron nitride, 20% chemical sunscreen, 2% physical sunscreen (nano titanium dioxide), 17% additives and 60% water.

[0188] The sunscreen composition was prepared according to the method of Example 1.

[0189] Comparative Example 4

[0190] The sunscreen composition of Comparative Example 4 is essentially the same as that of Example 1, except that "1% boron nitride 2%, 2% silica 1%, 58% water" is replaced with "5% boron nitride 2%, 56% water". Specifically, the sunscreen composition consists of the following components by mass fraction:

[0191] 5% boron nitride, 20% chemical sunscreen, 2% physical sunscreen (nano titanium dioxide), 17% additives and 56% water.

[0192] The sunscreen composition was prepared according to the method of Example 1.

[0193] Comparative Example 5

[0194] The sunscreen composition of Comparative Example 5 is essentially the same as that of Example 1, except that "1% boron nitride 2, 2% silica 1, 58% water" is replaced with "5% boron nitride 3, 56% water". Specifically, the sunscreen composition consists of the following components by mass fraction:

[0195] 5% boron nitride, 20% chemical sunscreen, 2% physical sunscreen (nano titanium dioxide), 17% additives and 56% water.

[0196] The sunscreen composition was prepared according to the method of Example 1.

[0197] Comparative Example 6

[0198] The sunscreen composition of Comparative Example 6 is essentially the same as that of Example 1, except that boron nitride 2⁻ is replaced with an equal mass of water. Specifically, the sunscreen composition consists of the following components by mass fraction:

[0199] 2% silica, 20% chemical sunscreen, 2% physical sunscreen (nano titanium dioxide), 17% additives and 59% water.

[0200] The sunscreen composition was prepared according to the method of Example 1.

[0201] Comparative Example 7

[0202] The sunscreen composition of Comparative Example 7 is essentially the same as that of Example 1, except that "1% boron nitride 2%, 2% silica 1%, 58% water" is replaced with "10% silica 1%, 51% water". Specifically, the sunscreen composition consists of the following components by mass fraction:

[0203] 10% silica, 20% chemical sunscreen, 2% physical sunscreen (nano titanium dioxide), 17% additives and 51% water.

[0204] The sunscreen composition was prepared according to the method of Example 1.

[0205] Comparative Example 8

[0206] The sunscreen composition of Comparative Example 8 is essentially the same as that of Example 1, except that "1% boron nitride 2, 2% silica 1, 58% water" is replaced with "5% silica 3, 56% water". Specifically, the sunscreen composition consists of the following components by mass fraction:

[0207] 5% silica, 20% chemical sunscreen, 2% physical sunscreen (nano titanium dioxide), 17% additives and 56% water.

[0208] The sunscreen composition was prepared according to the method of Example 1.

[0209] Comparative Example 9

[0210] The sunscreen composition of Comparative Example 9 is essentially the same as that of Example 1, except that "1% boron nitride 2%, 2% silica 1%, 58% water" is replaced with "5% silica 4%, 56% water". Specifically, the sunscreen composition consists of the following components by mass fraction:

[0211] 5% silica, 20% chemical sunscreen, 2% physical sunscreen (nano titanium dioxide), 17% additives and 56% water.

[0212] The sunscreen composition was prepared according to the method of Example 1.

[0213] Comparative Example 10

[0214] The sunscreen composition of Comparative Example 10 is essentially the same as that of Example 1, except that boron nitride 2 is replaced with an equal mass of boron nitride 1. Specifically, the sunscreen composition consists of the following components by mass fraction:

[0215] 1% boron nitride, 2% silica, 20% chemical sunscreen, 2% physical sunscreen (nano titanium dioxide), 17% additives and the balance 58% water.

[0216] The sunscreen composition was prepared according to the method of Example 1.

[0217] Comparative Example 11

[0218] The sunscreen composition of Comparative Example 11 is essentially the same as that of Example 1, except that silica 1 is replaced with an equal mass of silica 3. Specifically, the sunscreen composition consists of the following components by mass fraction:

[0219] 1% boron nitride, 2% silica, 20% chemical sunscreen, 2% physical sunscreen (nano titanium dioxide), 17% additives and the balance 58% water.

[0220] The sunscreen composition was prepared according to the method of Example 1.

[0221] Comparative Example 12

[0222] The sunscreen composition of Comparative Example 12 is essentially the same as that of Example 1, except that silica 1 is replaced with an equal mass of silica 4. Specifically, the sunscreen composition consists of the following components by mass fraction:

[0223] 1% boron nitride, 2% silica, 20% chemical sunscreen, 2% physical sunscreen (nano titanium dioxide), 17% additives and the balance 58% water.

[0224] The sunscreen composition was prepared according to the method of Example 1.

[0225] Experimental Example 1

[0226] Using the sunscreen compositions of the examples and comparative examples as samples, the in vitro sun protection value (SPF value, sun protection index) of the samples was tested using a Labsphere UV-2000S ultraviolet analyzer, according to the COLIPA 2011 standard method. The sun protection efficacy of the samples is shown in Table 1.

[0227] Table 1. Sunscreen efficacy of the samples

[0228]

[0229] The results in Table 1 show that, compared with Comparative Examples 1-12, the SPF values ​​of the sunscreen compositions of Examples 1-9 of this application increased from 44-62 to 67-92.

[0230] Comparing Example 1 of this application with Comparative Examples 1, 3, and 6, the sunscreen composition of Comparative Example 1 did not use boron nitride and silica, and its SPF value was 44. Compared with Comparative Example 1, Comparative Example 3 used 1% by mass of boron nitride 2, and its SPF value was not improved; Comparative Example 6 used 2% by mass of silica 1, and its SPF value was increased by 18%; Example 1 used 1% by mass of boron nitride 2 and 2% by mass of silica 1, and its SPF value was increased by 52%. It can be seen that Example 1 of this application, by using boron nitride 2 and silica 1 in combination, achieves a synergistic effect, which can significantly improve the sunscreen efficacy of the sunscreen composition.

[0231] Comparing Example 1 of this application with Comparative Examples 10-12, it can be seen that, under the same conditions of boron nitride and silica usage, compared with Comparative Examples 10-12, Example 1 of this application, using boron nitride 2 and silica 1, increases the SPF value from 55-62 to 67. This indicates that the use of boron nitride with an average particle size of 6μm-12μm and an oil absorption value of 50 g / 100g-100 g / 100g, and silica with an average particle size of 3μm-7μm and an oil absorption value of 60 g / 100g-130 g / 100g, can significantly improve the sun protection efficacy of the sunscreen composition.

[0232] The technical features of the above embodiments can be combined in any way. For the sake of brevity, not all possible combinations of the technical features in the above embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0233] The embodiments described above are merely illustrative of several implementation methods of this application, and while the descriptions are relatively specific and detailed, they should not be construed as limiting the scope of the patent application. It should be noted that those skilled in the art can make various modifications and improvements without departing from the concept of this application, and these all fall within the protection scope of this application. Therefore, the protection scope of this patent application should be determined by the appended claims.

Claims

1. A sunscreen composition, characterized in that, Components including the following mass fractions: 1%-2% boron nitride, 2%-6% silica, 15%-25% chemical sunscreen, 10%-30% additives and 37%-72% water; The boron nitride described therein has the following properties: average particle size of 6μm-12μm and oil absorption value of 50 g / 100g-100 g / 100g. The silica has the following characteristics: average particle size of 3μm-7μm and oil absorption value of 60 g / 100g-130 g / 100g.

2. The sunscreen composition according to claim 1, characterized in that, The boron nitride is boron nitride that has undergone surface treatment with a polydimethylsiloxane derivative.

3. The sunscreen composition according to claim 2, characterized in that, In the boron nitride surface-treated with polydimethylsiloxane derivatives, the polydimethylsiloxane derivatives include PEG-12 polydimethylsiloxane.

4. The sunscreen composition according to any one of claims 1-3, characterized in that, It meets at least one of the following characteristics: (1) In the sunscreen composition, the boron nitride has a mass fraction of 1%-1.5%, and the silica has a mass fraction of 3%-4.5%; (2) The boron nitride satisfies the following conditions: average particle size of 6μm-12μm, and oil absorption value of 50 g / 100g-60 g / 100g; (3) The silica satisfies the following conditions: average particle size of 3μm-7μm, and oil absorption value of 90 g / 100g-100 g / 100g; (4) The chemical sunscreen agent includes at least one of the following: ethylhexyl p-methoxycinnamate, butyl methoxydibenzoylmethane, benzyl camphor sulfonic acid and its salts, bis-ethylhexyloxyphenol methoxyphenyl triazine, camphor benzalkonium methyl sulfate, diethylamino hydroxybenzoyl hexyl benzoate, diethylhexyl butamidotriazinone, disodium phenyl dibenzimidazole tetrasulfonate, cresoltrazol trisiloxane, dimethyl PABA ethylhexyl ester, ethylhexyl salicylate, ethylhexyl triazinone, humosasulfate, isoamyl p-methoxycinnamate, methylene bis-benzotriazolyl tetramethyl butylphenol, PEG-25 p-aminobenzoic acid, phenyl benzyl mitomazole sulfonic acid and its salts, polyacrylamide methyl benzyl camphor, and polysiloxane-15; (5) The sunscreen composition further includes 2%-5% by mass of a physical sunscreen agent; The physical sunscreen agent includes at least one of nano titanium dioxide, nano cerium dioxide, and nano iron oxide.

5. The sunscreen composition according to any one of claims 1-3, characterized in that, The additives include at least one of the following: humectants, film-forming agents, skin-moisturizing agents, emulsifiers, thickeners, and preservatives.

6. The sunscreen composition according to claim 5, characterized in that, It meets at least one of the following characteristics: (1) The moisturizer includes at least one of butylene glycol, glycerin and propylene glycol; (2) The film-forming agent includes at least one of polydimethylsiloxane, acrylate copolymers and polyurethane copolymers; (3) The emollient includes at least one of diisopropyl sebacate, cetearyl alcohol, butyl octyl salicylate, C12-15 alcohol benzoate and dibutyl adipate; (4) The emulsifier includes at least one of cetyl phosphate potassium, cetearyl glucoside and sodium stearoyl glutamate; (5) The thickener includes at least one of sodium polyacrylate, xanthan gum, carbomer, hydroxyethyl cellulose, acrylate, guar gum and gum arabic; (6) The preservatives include at least one of phenoxyethanol, octyl glycol, ethylhexylglycerin, 1,2-pentanediol and hexanediol.

7. A method for preparing a sunscreen composition, characterized in that, Includes the following steps: Mix the chemical sunscreen, film-forming agent, and emollient evenly to prepare solution A; Physical sunscreen and silica are added to solution A and mixed evenly to prepare composition A; After mixing water, emulsifier, humectant, preservative A and thickener A, boron nitride is added and mixed evenly to prepare solution B; The composition A is added to the solution B and homogenized and emulsified. Then, thickener B is added and homogenization is continued. After all components are emulsified and dispersed evenly, the mixture is stirred and cooled. During the stirring and cooling process, preservative B is added, and stirring and cooling are continued to prepare the sunscreen composition. In the sunscreen composition, the mass fraction of boron nitride is 1%-2%, the mass fraction of silica is 2%-6%, and the mass fraction of chemical sunscreen agent is 15%-25%. The boron nitride meets the following requirements: average particle size of 6μm-12μm, and oil absorption value of 50 g / 100g-100 g / 100g; The silica has the following characteristics: average particle size of 3μm-7μm and oil absorption value of 60 g / 100g-130 g / 100g.

8. The method for preparing the sunscreen composition according to claim 7, characterized in that, The chemical sunscreen agent includes at least one of ethylhexyl salicylate, ethylhexyl methoxycinnamate, bis-ethylhexyloxyphenol methoxyphenyl triazine, ethylhexyl triazine ketone, methylene bis-benzotriazolyl tetramethylbutylphenol, and polysiloxane-15. And / or, the film-forming agent includes polydimethylsiloxane; And / or, the emollient includes diisopropyl sebacic acid and cetearyl alcohol; And / or, the physical sunscreen agent includes nano-titanium dioxide; And / or, in the sunscreen composition, the mass fraction of the physical sunscreen agent is 2%-5%; And / or, the emulsifier includes potassium cetyl phosphate; And / or, the humectant includes butylene glycol; And / or, the preservative A includes octyl glycol; And / or, the thickener A includes xanthan gum; And / or, the boron nitride is boron nitride surface-treated with PEG-12 polydimethylsiloxane; And / or, the thickener B comprises sodium polyacrylate; And / or, the preservative B includes phenoxyethanol; And / or, the boron nitride satisfies the following conditions: average particle size of 6μm-12μm, and oil absorption value of 50 g / 100g-60 g / 100g; And / or, the silica satisfies the following conditions: average particle size of 3μm-7μm, and oil absorption value of 90 g / 100g-100 g / 100g.

9. A sunscreen formulation, characterized in that, The raw materials include: the sunscreen composition according to any one of claims 1-6 or the sunscreen composition prepared by the method of preparing the sunscreen composition according to claim 7 or 8.

10. The sunscreen formulation according to claim 9, characterized in that, Sunscreen formulations can be in the form of emulsions or creams.